2019
DOI: 10.1016/j.jvs.2018.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Implications of secondary aortic intervention after thoracic endovascular aortic repair for acute and chronic type B dissection

Abstract: Background: Thoracic endovascular aortic repair (TEVAR) has become a mainstay of therapy for acute and chronic type B aortic dissection (TBAD). Dynamic aortic morphologic changes, untreated dissected aorta, and persistent false lumen perfusion have significant consequences for reintervention after TEVAR for TBAD. However, few reports contrast differences in secondary aortic intervention (SAI) after TEVAR for TBAD or describe their influence on mortality. This analysis examined incidence, timing, and types of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 38 publications
(56 reference statements)
2
24
0
Order By: Relevance
“…Chronic TBAD was found to have poorer aortic remodeling during follow-up. 39,40,41 Based on a large sample, our findings could raise further concern about the early postoperative complications of chronic patients. Eggebrecht et al found that more rigid intimal flaps and non-compliant aortic walls in chronic patients caused more fatal in-hospital complications after TEVAR, such as aorto-esophageal fistula.…”
Section: Discussionmentioning
confidence: 78%
“…Chronic TBAD was found to have poorer aortic remodeling during follow-up. 39,40,41 Based on a large sample, our findings could raise further concern about the early postoperative complications of chronic patients. Eggebrecht et al found that more rigid intimal flaps and non-compliant aortic walls in chronic patients caused more fatal in-hospital complications after TEVAR, such as aorto-esophageal fistula.…”
Section: Discussionmentioning
confidence: 78%
“…Looking at the big picture, long-term instability of aortic endografts, both abdominal and thoracic, remains a concern in up to one-fourth of cases. 3,5,6 Such issues make lifelong surveillance mandatory, a point that has become more important since the management trends for aortic pathologies have expanded the treatment to younger patients with longer life expectancies, in addition to octo-and nonagenarians. 1 The complexity of thoracic aortic diseases, their inaccessibility to ultrasound examination, and the extreme variability of postoperative complications compel us to submit our patients to CTA or magnetic resonance angiography at 30 days, 6 months, and then yearly for the rest of their lives.…”
mentioning
confidence: 99%
“…Such feelings are more frequent after we treat aortic patients presenting with short, tortuous, and calcified necks, basically those patients who are totally outside the instructions for use and who may represent up to 80% of our patient volume. 1-3…”
mentioning
confidence: 99%
See 2 more Smart Citations